Volatile and sensory composition of Brazilian Muscat sparkling wine and Asti. Issue 4 (5th February 2021) - Marcon, Ângela Rossi; Delamare, Ana Paula Longaray; Schwarz, Luisa Vivian; Pasini, Luca; Versari, Andrea; Parpinello, Giuseppina Paola; Echeverrigaray, Sergio
Abstract: The aim of this study is to evaluate Muscat sparkling wines from the traditional Asti region (Italy) and the new geographical indication "IG Farroupilha" (Brazil). We analyzed 23 commercial Muscat sparkling wines from Asti and Farroupilha. Sample characterization of the aromatic profile by headspace‐solid phase microextraction and gas chromatography detector yielded a total of 32 targeted components in Muscat wines. The multivariate analysis of data differentiates the Muscat sparkling wines based on origin: Brazilian or Italian. The main quantitative differences between wines are residual sugar, sulfite content, isoamyl acetate, hexyl acetate, limonene, rose oxide, linalool, and citronellol. The sensory analysis confirmed that Brazilian wines were less sweet with freshener aroma, whereas the Italian wines were more intense in aroma, complex, and sweet. These peculiarities can be associated with terroir, including technological processes that may be tailored to fit different wine styles for particular markets. Practical applications: The chemical and sensorial characterizations of sparkling wines produced in regions with geographical indication are important to differentiate products made in different regions.